Concrete composition
By using fine-milled steel water-milling powder, plenamine materials and activated lime in concrete, combined with low water-powder ratio and accelerator, the problems of delay in the initial strength development and increase in self-shrinkage strain are solved, and the effects of high initial strength and low self-shrinkage strain are achieved, while reducing carbon dioxide emissions.
Patent Information
- Application Number
- JP2023180376
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
AI Technical Summary
The existing concrete that uses a large amount of fine-milled steel water-milling powder has delayed the initial strength development and the self-shrinkage strain increases, resulting in an extended construction cycle and an increase in the risk of concrete cracks. It is difficult to simultaneously increase the initial strength and suppress self-shrinkage strain.
The hydraulic powder containing finely ground steel water-milling powder, plenamine material and activated lime, combined with low water-powder ratio and accelerator, and using shrinkage reducer and light calcium carbonate, is used to make concrete with high initial strength and low self-shrinkage strain.
It is achieved without increasing the gouache ratio, which increases the initial strength of concrete and suppresses self-shrinkage strain, shortens the construction cycle and reduces the risk of concrete cracks, and reduces carbon dioxide emissions.
Smart Images

Figure 2025070219000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention is 2 The present invention relates to a concrete composition that can contribute to reducing emissions, and that contains a large amount of ground granulated blast furnace slag. [Background technology]
[0002] CO from the production of materials such as concrete and mortar 2 Nearly 90% of emissions are due to the production of Portland cement. Therefore, by using ground granulated blast furnace slag or fly ash instead of Portland cement, CO emissions can be reduced. 2 Emissions can be significantly reduced.
[0003] For example, the commonly available blast-furnace cement type B has 40-50% by mass of Portland cement replaced with ground granulated blast-furnace slag. Concrete using blast-furnace cement type B has a lower CO2 emission rate than concrete using only Portland cement. 2 The reduction rate is about 30-40%. 2 In order to reduce CO emissions as much as possible, concrete has been developed that uses ground granulated blast furnace slag, expansive agent, and hydrated lime instead of Portland cement. 2 The reduction rate will be approximately 80%.
[0004] Patent Document 1 also proposes a concrete composition that uses a large amount of ground granulated blast furnace slag. In detail, Patent Document 1 describes that the binder contains 70% by mass or more and 100% by mass or less of blast furnace cement with respect to the total mass of the binder, and that the blast furnace cement has an average specific surface area of 2500 to 8000 cm 2 The mixture is made of 45 to 75 mass% granulated blast furnace slag with a molecular weight of 1.0 to 1.5 g / g, 20 to 50 mass% Portland cement, and sulfates in the form of SO 3 A concrete composition containing, in terms of mass percent, 1.0 to 4.5% by mass is disclosed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-151517 A Summary of the Invention [Problem to be solved by the invention]
[0006] Concrete that uses a large amount of ground granulated blast furnace slag as described in Patent Document 1 has a delayed "initial strength development" compared to conventional concrete that uses only Portland cement because the amount of cement is small. This delayed initial strength development leads to a delayed removal of the formwork during construction.
[0007] In addition, concrete shrinkage can be broadly divided into drying shrinkage (strain caused by water loss due to drying) and autogenous shrinkage (strain caused by self-drying due to hydration). Conventional concrete in the normal strength range that uses only Portland cement has a relatively small autogenous shrinkage strain, which is not a major problem. On the other hand, concrete that uses a large amount of ground granulated blast furnace slag is known to cause an increase in "autogenous shrinkage strain" depending on the curing temperature (Architectural Institute of Japan, "Design and Construction Guidelines (Draft) and Commentary for Reinforced Concrete Buildings Using Blast-Furnace Cement or Ground Granulated Blast-Furnace Slag"). Furthermore, because an increase in autogenous shrinkage strain increases the risk of cracks occurring in concrete components, there is often a demand for mixing, design, and construction measures to prevent cracks.
[0008] In this way, for concrete that uses large amounts of ground granulated blast furnace slag, improving the "early strength development" (more specifically, improving the compressive strength in the early stages of the material's life) and suppressing "autogenous shrinkage strain" are extremely important factors from the standpoint of shortening construction time and ensuring quality. Here, methods for improving the "initial strength development" include reducing the water-powder ratio and adding a hardening accelerator, but simply applying these methods will increase the "autogenous shrinkage strain." In other words, it was difficult to simultaneously improve "early strength development" and suppress "autogenous shrinkage strain" for concrete that used a large amount of ground granulated blast furnace slag.
[0009] Therefore, an object of the present invention is to provide a concrete composition that can improve the initial strength development and suppress autogenous shrinkage strain. [Means for solving the problem]
[0010] The above problems can be solved by the following measures. The concrete composition according to the present invention is a concrete composition containing hydraulic powder, water, aggregate, and chemical admixture, wherein the hydraulic powder contains ground granulated blast furnace slag, an expansive agent, and hydrated lime, the content of the ground granulated blast furnace slag is 80 parts by mass or more per 100 parts by mass of the hydraulic powder, the chemical admixture is a shrinkage reducing agent, has a water-powder ratio of 28% or less, and contains a hardening accelerator. According to the present invention, since the composition contains a shrinkage reducing agent and satisfies at least one of the following conditions: the water-powder ratio is 28% or less, and a hardening accelerator is contained, even if the content of ground granulated blast furnace slag is high, it is possible to simultaneously improve the initial strength development and suppress autogenous shrinkage strain. In the concrete composition according to the present invention, the shrinkage reducing agent preferably contains an alkylene glycol derivative, a hydrocarbon compound and a glycol ether derivative, or a special polyoxyalkylene glycol. Also, in the concrete composition according to the present invention, the hardening accelerator preferably contains at least one of a nitrate ion and a nitrite ion. According to the present invention, since the shrinkage reducing agent and the hardening accelerator contain the specified components, it is possible to effectively improve the initial strength development and suppress autogenous shrinkage distortion. The concrete composition according to the present invention is 2 From the viewpoint of reducing emissions, it is preferable that the mixture does not contain cement. The concrete composition according to the present invention has a compressive strength of 10 N / mm 2 More preferably, it is equal to or greater than this. According to the present invention, by specifying the compressive strength at one day to be equal to or greater than a predetermined value, the effect of improving the initial strength development can be more reliably achieved. In the concrete composition according to the present invention, the content of the shrinkage reducing agent is preferably 0.5 to 2.5 parts by mass based on 100 parts by mass of the ground granulated blast furnace slag. According to the present invention, by specifying the content of the shrinkage reducing agent, the effect of suppressing autogenous shrinkage distortion can be more reliably achieved. The concrete composition according to the present invention preferably contains precipitated calcium carbonate. According to the present invention, by containing light calcium carbonate, the concrete is provided with CO 2 By immobilizing CO 2 Emissions can be reduced even more dramatically. Effect of the Invention
[0011] The concrete composition according to the present invention has improved early strength development and suppressed autogenous shrinkage strain. [Brief description of the drawings]
[0012] [Figure 1] 1 is a graph showing the compressive strength of each sample in Example 1. [Diagram 2] 1 is a graph showing the ratio of autogenous shrinkage strain of each sample in Example 1. [Diagram 3] 1 is a graph showing the relationship between the compressive strength and the autogenous shrinkage strain ratio of each sample in Example 1. [Figure 4] 1 is a graph showing the compressive strength of each sample in Example 2. [Diagram 5] 1 is a graph showing the ratio of autogenous shrinkage strain of each sample in Example 2. [Figure 6] 1 is a graph showing the relationship between the compressive strength and the autogenous shrinkage strain ratio of each sample in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The concrete composition according to this embodiment will be described below. [Concrete composition] The concrete composition according to the present embodiment is a composition containing hydraulic powder, water, aggregate, and chemical admixture, the hydraulic powder containing ground granulated blast furnace slag, an expansive agent, and hydrated lime, and the chemical admixture is a shrinkage reducing agent. The concrete composition according to the present embodiment satisfies at least one of the following: the water-powder ratio is equal to or less than a predetermined value, and the concrete composition contains a hardening accelerator. Each of the constituent elements will be described in detail below.
[0014] (hydraulic powder) Hydraulic powder is a powdery substance that hardens by hydration. Specifically, hydraulic powder includes ground granulated blast furnace slag, expansive material, and hydrated lime. Hydraulic powder may also contain fly ash, silica fume, etc. In the present invention, the hydraulic powder may contain various types of cement (JISR5210:2009), such as ordinary Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, and sulfate-resistant Portland cement. 2 From the viewpoint of reducing emissions, the content of these cements is preferably small, and it is particularly preferable that these cements are not contained.
[0015] (Hydraulic powder: finely ground blast furnace slag) Ground granulated blast furnace slag is made by drying and grinding granulated blast furnace slag, or by adding gypsum to this, and is specified in JISA6206:2013. The content of the ground granulated blast furnace slag is preferably 80 parts by mass or more, more preferably 82 parts by mass or more, and more preferably 83 parts by mass or more, per 100 parts by mass of the hydraulic powder. By ensuring that the content of ground granulated blast furnace slag is above a certain value, the cement content is reduced, and CO 2 While the amount of emissions can be reduced, the problem of the present invention (the difficulty of simultaneously achieving both improvement in initial strength development and suppression of autogenous shrinkage distortion) becomes apparent. The upper limit of the content of the ground granulated blast furnace slag is not particularly limited, but is, for example, 95 parts by mass or less, or 90 parts by mass or less, relative to 100 parts by mass of the hydraulic powder.
[0016] (Hydraulic powder: expansion material) An expansive agent is an admixture that has the effect of expanding concrete or mortar, and is defined in JISA6202:2017. The content of the expansive material is, for example, 1 part by mass or more, 3 parts by mass or more, 5 parts by mass or more, and 15 parts by mass or less, 12 parts by mass or less, 9 parts by mass or less, relative to 100 parts by mass of the hydraulic powder.
[0017] (Hydraulic powder: slaked lime) Slaked lime is calcium hydroxide (Ca(OH) 2 ). The content of slaked lime is, for example, 3 parts by mass or more, 5 parts by mass or more, 8 parts by mass or more, and 15 parts by mass or less, 12 parts by mass or less, 10 parts by mass or less, relative to 100 parts by mass of the hydraulic powder.
[0018] (Chemical admixtures) The chemical admixture is an admixture used to improve the properties of concrete, and is a shrinkage reducing agent (JIS A6211: 2020). By containing a shrinkage reducing agent in the concrete composition according to the present embodiment, the autogenous shrinkage strain can be suppressed even if the content of ground granulated blast furnace slag is large. The shrinkage reducing agent is preferably one containing an alkylene glycol derivative, a hydrocarbon compound and a glycol ether derivative, or a special polyoxyalkylene glycol, and more preferably one containing any of these as the main component.
[0019] The content of the shrinkage reducing agent is preferably 0.5 to 2.5 parts by mass, more preferably 0.5 to 1.5 parts by mass, per 100 parts by mass of the ground granulated blast furnace slag. By keeping the content of the shrinkage reducing agent within the specified range, the autogenous shrinkage distortion can be more reliably suppressed. In addition to the shrinkage reducing agents described above, the chemical admixtures may include thickening admixtures, retarding admixtures, separation reducing agents, air content regulators, setting accelerators, defoamers, high performance water reducing agents, high performance AE water reducing agents, etc. (JISA6204:2011). Any of the chemical admixtures other than the shrinkage reducing agents may be used alone or in combination of two or more.
[0020] In order to exert the effect of improving the initial strength development, the concrete composition according to this embodiment satisfies at least one of the following requirements: (requirement 1) the water-powder ratio is 28% or less, and (requirement 2) it contains a hardening accelerator.
[0021] (Requirement 1: water powder ratio) The water-powder ratio of the concrete composition according to the present embodiment is preferably 28% or less, more preferably 26% or less, and more preferably 25% or less. By making the water-powder ratio equal to or less than a predetermined value, the initial strength development of the concrete composition can be improved. The lower limit of the water / powder ratio is not particularly limited, but is, for example, 20% or more, or 22% or more. The "water-powder ratio" in the present invention is the ratio of unit water amount to unit powder amount, and the powder here is a concept that refers not only to hydraulic powder but also to all powders (i.e., a concept that includes not only the hydraulic powder described above but also light calcium carbonate, which will be described later). The water is not particularly limited, and tap water, sludge water, groundwater, etc. can be used.
[0022] (Requirement 2: Curing accelerator) The concrete composition according to the present embodiment contains a hardening accelerator. By containing the hardening accelerator, it is possible to improve the initial strength development of the concrete composition. A hardening accelerator is an admixture that has the effect of accelerating the hydration of materials, and is specified in JISA6204:2011. The hardening accelerator preferably contains at least one of nitrate ions and nitrite ions. The content of the hardening accelerator in the concrete composition is, for example, 10.0 kg / m 3 More than 15.0kg / m 3 More than 17.3kg / m 3 More than 40.0kg / m 3 Below, 37.0kg / m 3 Below, 34.0kg / m 3 The content of the hardening accelerator, based on the powder amount (P×%), is, for example, 2.0% or more, 3.0% or more, and 7.0% or less, 6.0% or less.
[0023] (aggregate) The aggregate is not particularly limited, and examples thereof include fine aggregate and coarse aggregate. Examples of fine aggregates include mountain sand, river sand, sea sand, crushed sand, silica sand, and lime sand, while examples of coarse aggregates include mountain gravel, river gravel, and sea gravel, all of which comply with JISA5005:2020. The content of fine aggregate in the concrete composition is, for example, 500 kg / m 3 More than 520kg / m 3 More than 800kg / m 3 Below 700kg / m 3 The content of the coarse aggregate in the concrete composition is, for example, 600 kg / m 3 More than 800kg / m 3 More than 1000kg / m 3 Below 900kg / m 3 The following is the result.
[0024] (Light calcium carbonate) Precipitated calcium carbonate is calcium carbonate produced by chemical reaction, CaCO 3 This is to be distinguished from ground calcium carbonate, which is produced by crushing and classifying raw materials whose main component is limestone, etc. And, if the raw material for light calcium carbonate is carbon dioxide contained in exhaust gas, etc., 2 (Eiji Owaki and Masaki Ogino, "Development of T-eConcrete / Carbon-Recycle, which has achieved carbon negative using carbon recycled materials," Cement & Concrete 900, pp. 70-75.) Therefore, by including light calcium carbonate in the concrete composition, CO 2 This allows for greater reductions in emissions. The content of light calcium carbonate in the concrete composition is, for example, 100 kg / m 3 More than 200kg / m 3 More than 400kg / m 3 Below 300kg / m 3 The following is the result.
[0025] (Compressive strength at 1 day age) The concrete composition according to this embodiment has a compressive strength of 10 N / mm 2 More preferably, the above is true. By making the compressive strength of the concrete composition at one day equal to or greater than a predetermined value, the effect of improving the initial strength development can be reliably achieved. The compressive strength may be measured using a method conforming to JISA1108:2018.
[0026] (others) The concrete composition according to this embodiment may contain, as appropriate, conventionally known materials (fibers, etc.) used in concrete, as long as the desired effects of the present invention are not impaired. EXAMPLES
[0027] [Example 1] Example 1 was a test on a concrete composition in which no cement was used and ground granulated blast furnace slag was hardened with an expansive agent and hydrated lime, and the effects of the water-powder ratio and the shrinkage-reducing agent were mainly confirmed.
[0028] (material) The compositions of the samples used in Example 1 are shown in Table 1. The materials shown in Table 1 are as follows: BFS: Blast furnace slag powder, density 2.89g / cm 3 ,JISA6206 compliant product EX1: Expanding agent, density 3.15g / cm 3 ,JISA6202 compliant product EX2: Expanding agent, density 3.17g / cm 3 ,JISA6202 compliant product CH: Slaked lime (special issue) Density 2.20g / cm 3 ,JISR9001 compliant product LSP: Ground calcium carbonate powder, density 2.72g / cm 3 S: Mixed sand JISA5308 Annex A compliant product G: Crushed stone 2005 JISA5308 Appendix A compliant product Type of shrinkage reducing agent (main ingredient is based on manufacturer catalog / data sheet) *1 MasterLife (registered trademark) SRA900 (Pozzolith Solutions, Inc.) Main ingredient: Alkylene glycol derivative *2 Shrink Guard (Floric Co., Ltd.) Main components: Hydrocarbon compounds and glycol ether derivatives *3 Water-retaining shrinkage reducing agent (Nippon Shokubai Co., Ltd.) Main ingredient: Special polyoxyalkylene glycol
[0029] Of the samples in Table 1, the ratio of parts by mass of the hydraulic powder in Comparative Example 1-1 was 84:8:8 (ground granulated blast furnace slag (BFS):expansion agent (EX1):slaked lime (CH), and the ratio of parts by mass of the hydraulic powder in Comparative Examples 1-2, 1-3, and Examples 1-1 to 1-4 was 87:5:8 (ground granulated blast furnace slag (BFS):expansion agent (EX2):slaked lime (CH). The shrinkage reducing agent content in Examples 1-1 to 1-4 was 0.5 to 1.1 parts by mass relative to 100 parts by mass of ground granulated blast furnace slag. The shrinkage reducing agent used was a product conforming to JISA6211:2020 and is generally used to suppress drying shrinkage, and the content was within the standard range indicated by each manufacturer.
[0030] [Table 1]
[0031] (Test content: Compressive strength) The compressive strength was measured in accordance with JISA1108:2018, and the specimens were sealed and cured at 20°C. The compressive strength of each sample was measured at ages of 1 day, 2 days, and 7 days.
[0032] (Test content: Autogenous shrinkage strain) The autogenous shrinkage strain was measured in accordance with JCI-SAS2 (Test Method for Autogenous Shrinkage and Expansion of Cement Paste, Mortar, and Concrete (Draft)), with an embedded strain gauge set in the center of a 100 x 100 x 400 mm specimen. The specimen was removed from the mold after 1 day (24 hours) of age, and the entire surface was sealed with aluminum tape to prevent drying. The curing temperature was 20°C, and the strain of the specimen was measured after 7 and 28 days of age. The ratio of the autogenous shrinkage strain of each sample was calculated based on the measured values of strain of Comparative Example 1-3 at ages of 7 and 28 days. For example, the ratio of the autogenous shrinkage strain of Example 1-1 at age of 7 days was calculated as "measured value of strain of Example 1-1 at age of 7 days / measured value of strain of Comparative Example 1-3 at age of 7 days."
[0033] Example 1: Discussion of Results FIG. 1 is a graph showing the compressive strength of each sample in Example 1. The compressive strength at one day was 2.6N / mm for Comparative Example 1-1. 2 Comparative Example 1-2, which has a water / powder ratio that is about 5% lower than that of Comparative Example 1-1, has a strength of 9.5 N / mm2 Furthermore, Comparative Example 1-3, which has a 5% lower water / powder ratio, is 15N / mm 2 From these results, it was confirmed that the initial strength development was improved by decreasing the water-powder ratio. In addition, in Examples 1-1 to 1-4 in which a shrinkage reducing agent was added to Comparative Example 1-3, the compressive strength at 1 day was 11 to 14 N / mm 2 This was slightly smaller than that of Comparative Example 1-3, but larger than that of Comparative Examples 1-1 and 1-2. From this result, it was confirmed that the addition of a shrinkage-reducing agent did not significantly reduce the initial compressive strength.
[0034] FIG. 2 is a graph showing the autogenous shrinkage strain ratio of each sample in Example 1. The autogenous shrinkage strain of Comparative Example 1-1 and Comparative Example 1-2 was about 30 to 50% smaller than that of Comparative Example 1-3. Therefore, it was confirmed that as the water-powder ratio decreased from Comparative Example 1-1 to 1-2 to 1-3, the initial strength development improved, but the autogenous shrinkage strain increased. On the other hand, the autogenous shrinkage strain of Examples 1-1 to 1-4 was approximately 10 to 30% smaller than that of Comparative Example 1-3, and it was confirmed that the autogenous shrinkage strain could be suppressed by adding a shrinkage reducing agent.
[0035] FIG. 3 is a graph showing the relationship between the compressive strength (at an age of 1 day) and the autogenous shrinkage strain (at an age of 28 days) of each sample in Example 1. The Architectural Institute of Japan's "Standard Specifications for Construction Works and Commentary JASS10 Precast Reinforced Concrete Construction" recommends a guideline of 8 to 12 N / mm 2 Therefore, the standard for judging the initial strength development is set as an average value of 10N / mm 2 In addition, the criterion for determining autogenous shrinkage strain is a ratio of autogenous shrinkage strain of 0.9 or less. These criteria are shown by the bold lines in FIG. 3, and items that satisfy both criteria fall within the range enclosed by the bold lines in the lower right corner of FIG. In Comparative Example 1-1, the compressive strength at one day is small, and by decreasing the water-powder ratio, the compressive strength at one day is improved as in Comparative Examples 1-2 and 1-3. On the other hand, the autogenous shrinkage strain increases as in Comparative Examples 1-2 and 1-3 by decreasing the water-powder ratio from Comparative Example 1-1. Here, Examples 1-1 to 1-4, in which various shrinkage reducing agents were added to Comparative Example 1-3, were able to not only reduce the autogenous shrinkage strain more than Comparative Example 1-3, but also increase the compressive strength at 1 day more than Comparative Example 1-2. From these results, it was confirmed that the present invention (Examples 1-1 to 1-4) can improve the initial strength development more than Comparative Example 1-1 and suppress the autogenous shrinkage distortion more than Comparative Example 1-3 by having a water-powder ratio below a predetermined value and containing a shrinkage reducing agent.
[0036] [Example 2] In Example 2, a test was conducted on a concrete composition in which no cement was used, ground granulated blast furnace slag was hardened with an expansive agent and hydrated lime, and light calcium carbonate was further added, and the effects of the hardening accelerator and shrinkage-reducing agent were mainly confirmed.
[0037] (material) The compositions of the samples used in Example 2 are shown in Table 2. The materials shown in Table 2 are as follows: Note that the explanation of the materials already shown in Example 1 will be omitted. EX: Expanding agent Density 3.15g / cm 3 ,JIS A 6202 compliant product Cc1: Light calcium carbonate 1, density 2.72g / cm 3 Cc2: Light calcium carbonate 2, density 2.52g / cm 3 Hardening accelerator: Master Set FZP99, manufactured by Pozzolith Solutions, nitrate ion equivalent content 24% by mass, nitrite ion equivalent content 24% by mass (JIS A6204 compliant product)
[0038] The ratio of the hydraulic powder parts by mass of each sample in Table 2 was granulated blast furnace slag (BFS):expansive material (EX):slaked lime (CH) = 83:9:8. The content of the shrinkage reducing agent in Example 1-1 was 1.1 parts by mass per 100 parts by mass of ground granulated blast furnace slag. The light calcium carbonate was hydrated lime (Ca(OH) 2 ) to carbon dioxide (CO 2 ) is a fine powder produced by reacting two different types (Cc1 and Cc2) from different manufacturers.
[0039] [Table 2]
[0040] (Test contents: compressive strength, autogenous shrinkage strain) The methods for measuring the compressive strength and autogenous shrinkage strain in Example 2 were the same as those in Example 1. The method of calculating the ratio of autogenous shrinkage strain of each sample was different from that of Example 1, and the calculation was performed based on the measured values of strain of Comparative Example 2-2 at material ages of 7 days and 28 days.
[0041] Example 2: Discussion of Results FIG. 4 is a graph showing the compressive strength of each sample in Example 2. FIG. 5 is a graph showing the autogenous shrinkage strain ratio of each sample in Example 2. When comparing Comparative Examples 1-1 and 1-2, the addition of a hardening accelerator increases the compressive strength at 1 day (Fig. 4), but the autogenous shrinkage strain at 28 days also increases (Fig. 5). From these results, it was confirmed that it is difficult to simultaneously improve the initial strength development and suppress the autogenous shrinkage strain by simply adding a hardening accelerator. On the other hand, in Example 2-1, not only a hardening accelerator but also a shrinkage reducing agent was added, and compared to Comparative Example 2-2, it was confirmed that the autogenous shrinkage strain ratio at 28 days of age could be significantly reduced (Figure 5) without reducing the compressive strength at 1 day of age (Figure 4).
[0042] FIG. 6 is a graph showing the relationship between the compressive strength (at an age of 1 day) and the autogenous shrinkage strain (at an age of 28 days) of each sample in Example 2. In addition, in Fig. 6, as in Fig. 3, the criterion for judging the initial strength development is a compressive strength of 10 N / mm 2 The criterion for determining autogenous shrinkage strain is an autogenous shrinkage strain ratio of 0.9 or less, and these criteria are indicated by thick lines. In Comparative Example 2-1, the compressive strength at one day is small, and the addition of a hardening accelerator improves the compressive strength at one day, as in Comparative Example 2-1. On the other hand, the autogenous shrinkage strain is increased, as in Comparative Example 2-2, by adding a hardening accelerator to Comparative Example 2-1. Here, Example 2-1, in which a shrinkage reducing agent is added to Comparative Example 2-2, is able to reduce the autogenous shrinkage strain more significantly than Comparative Example 2-2, and has a higher compressive strength at one day than Comparative Example 2-1. As a result, as shown in FIG. 6, Example 2-1 falls within the target performance range (the range surrounded by the thick line at the bottom right). From the above results, it was confirmed that the present invention (Example 2-1) can improve the initial strength development more than Comparative Example 2-1 and suppress the autogenous shrinkage distortion more than Comparative Example 2-2 by containing a hardening accelerator and a shrinkage reducing agent.
Claims
1. A concrete composition comprising hydraulic powder, water, aggregate, and chemical admixtures, The hydraulic powder contains ground granulated blast furnace slag, an expansive material, and slaked lime, The content of the ground granulated blast furnace slag is 80 parts by mass or more relative to 100 parts by mass of the hydraulic powder, The chemical admixture is a shrinkage reducing agent; A concrete composition characterized by satisfying at least one of the following requirements: a water-powder ratio of 28% or less; and containing a hardening accelerator.
2. 2. The concrete composition according to claim 1, characterized in that the shrinkage-reducing agent comprises an alkylene glycol derivative, a hydrocarbon compound and a glycol ether derivative, or a special polyoxyalkylene glycol.
3. 3. The concrete composition according to claim 1, wherein the hardening accelerator contains at least one of a nitrate ion and a nitrite ion.
4. 3. The concrete composition according to claim 1 or 2, characterized in that it does not contain cement.
5. The compressive strength at 1 day is 10N / mm 2 3. The concrete composition according to claim 1 or 2, characterized in that:
6. 3. The concrete composition according to claim 1, wherein the content of the shrinkage reducing agent is 0.5 to 2.5 parts by mass per 100 parts by mass of the ground granulated blast furnace slag.
7. 3. The concrete composition according to claim 1, further comprising precipitated calcium carbonate.
Citation Information
Patent Citations
Concrete composition and hardened concrete
JP2019151517A